HOMOEKONOMİKUS'UN GERÇEKLİĞİNİ SORGULAMAK: TÜRK ATASÖZLERİNDE İNSAN MANZARALARI - (:unkn) unknown (My University, 2016)
İktisat teorisinin temel varsayımlarından olan homoekonomikus tipolojisinin gerçekliği tartışmalıdır. Bu varsayım iktisadi analiz için bazı elverişliliklere sahip olsa da insan ekonomi ilişkisinde ekonominin insan için araç olmaktan amaç haline gelmesinde bir dönüm noktasıdır. Diğer taraftan modern ekonomilerin insanlara sunduğu refah ve tüketim imkânları homoekonomikusun teoriden gerçeğe dönüşme ihtimalini ortaya çıkarmaktadır. Dolayısıyla homoekonomikusla ilgili iki boyutlu bir problem söz konusudur. Makalede bu bağlamda ekonomi-insan ilişkisi tartışılarak, Türk atasözleri üzerinden bu tipolojinin gerçekliği sorgulanacaktır.

Homo economicus is one of the main assumptions in economic theory and reality of this typology is controversial. Even if the assumption of homo economicus has some convenience for economic analysis, this typology is a turning point on human-economy relation which transformed the economy to be the aim of life. On the other hand homo economicus assumption has probability to become a real in modern economies. In this article, these two aspects of homo economicus will be discussed and human-economy relation will be investigated by Turkish proverbs.
QUESTIONING THE REALITY OF HOMO ECONOMICUS: HUMAN VIEWS IN TURKISH PROVERBS
Keywords: Tarih